Mechanisms and characteristics of a low-loss split gate trench MOSFET with shield layer. (December 2021) - Wang, Zhengkang; Qiao, Ming; Li, Zhaoji; Zhang, Bo
Abstract: In this work, a split gate trench MOSFET (SGT) with shield layer (SL) is proposed to improve electrical characteristics. The SL modulates charge division of ionized donor atoms in drift region during depletion spreading. As a result, ionized donors electrically coupled to gate are dramatically reduced, thus lowering gate-drain charge (QGD ). On the other hand, the SL structure increases energy band of channel region to address drain induced barrier lowering (DIBL) issue while maintaining a lower channel length and doping concentration. Significant reductions in on-resistance (RON ), gate charge (QG ), and total power losses are confirmed by simulations. The proposed SGT with SL achieves a switching figure of merit (RON  × QG ) of 30.46 mΩnC, which is 35.5% smaller than conventional trench MOSFET technology, but almost without impacting other fundamental parameters.